2015
DOI: 10.1007/s11258-015-0519-z
|View full text |Cite
|
Sign up to set email alerts
|

Large pollen at high temperature: an adaptation to increased competition on the stigma?

Abstract: Pollen availability is a major constraint of plant reproductive success. Because pollen size tradesoff with the quantity of produced grains, the link between climate characteristics and the determination of pollen size is of fundamental importance. To minimize the rate of water loss due to desiccation, a plant should produce larger grains that also have a lower surface-to-volume ratio. We used a comparative analysis to examine the hypothesis predicting increase in pollen size as a response to desiccation inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 68 publications
1
24
3
2
Order By: Relevance
“…Consequently, we propose that due to the size variability in Cedrus atlantica pollen, and lack of evidence for climatic influence, it would not be possible to use this as a proxy for climate or environmental reconstruction, as differences in the size of fossil pollen may simply result from the observed natural variation in size between pollen grains. Our findings contrast the suggested climatic influence on grain size observed in other species (Ejsmond et al 2011(Ejsmond et al 2015Griener & Warny 2015), and underscore the need for further investigation of the complex controls on pollen grain size .…”
contrasting
confidence: 95%
See 3 more Smart Citations
“…Consequently, we propose that due to the size variability in Cedrus atlantica pollen, and lack of evidence for climatic influence, it would not be possible to use this as a proxy for climate or environmental reconstruction, as differences in the size of fossil pollen may simply result from the observed natural variation in size between pollen grains. Our findings contrast the suggested climatic influence on grain size observed in other species (Ejsmond et al 2011(Ejsmond et al 2015Griener & Warny 2015), and underscore the need for further investigation of the complex controls on pollen grain size .…”
contrasting
confidence: 95%
“…Ejsmond et al (2011) analysed eight Rosaceae species and found grain size increased under desiccation stress (determined by temperature, potential evapotranspiration and altitude). A positive relationship was also found between temperature and pollen size in 232 plant species from 11 taxonomic groups, suggesting possible climatic influence on size during the flowering period (Ejsmond et al 2015) and offering potential for pollen grain size to aid in reconstructions of past environments.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…A few studies have demonstrated that some environmental factors, such as temperature and drying conditions, does not affect this structure, but only change the size and chemical composition (Delph et al, 1997;Ejsmond et al, 2015). Schneider et al, (2009) reported another factor which can influence the pollen morphology (size), such as cytology (ploidy level), ecology, floral morphology or physiological constraints.…”
Section: Introductionmentioning
confidence: 99%